A pilot study on the positive rate of multi‐time point and multiple domain evaluation in cerebrospinal fluid tap test of patients with normal pressure hydrocephalus: Neuropsychiatry and behavioral neurology/Behavioral neurology. (7th December 2020) - Liu, Caiyan; Li, Jie; Huang, Xinying; Dong, Liling; Mao, Chenhui; Wei, Junji; Hou, Bo; Feng, Feng; Cui, Liying; Gao, Jing
Abstract: Background: The CSF tap test evaluation vary a lot in different medical center, which result in the wide range of sensitivity. Our study aimed to explore the effect of multi time point and multiple domain evaluation on the determination of CSF tap test results in patients with normal pressure hydrocephalus. Method: A total of 150 outpatients with NPH 2013‐2018 from the Department of Neurology of Peking Union Medical College Hospital were enrolled in this study. All patients underwent detailed neuropsychological (MMSE, MOCA, Trail Making Test, Digital Symbol, Stroop‐c test, Grooved pegboard test) and walking ability (10 meter walking test, 5 meter up and go test), and head MRI examination. Patients who did not complete the four time point's evaluation of CSF tap test to eliminate severe dementia and various reasons. The positive criteria were that the performance of either time or steps in walking test was 20% higher than the baseline level, or both were 10% higher. In the cognitive test, the score of any test is 20% higher than the baseline as a positive criterion. According to this standard, the positive rates of each evaluation test and three evaluation time points were calculated and compared. Result: The positive rate of 5 meter up and go test on 8 hours, 24 hours and 72 hours after CSF tap test was 40.6%, 42.0%, 48.9%, the positive rate of 10‐meter walking test was 35.8%, 30.9%, 40.7% respectively; the positive rate of Digital Symbol was 23.8%, 38.1%, 42.9% respectively; the positive rate of Trail Making T test was 38.7%, 45%, 57.9%; the positive rates of Stroop‐c performance were 27.0%, 39.3% and 49.1% respectively; the positive rates of Grooved pegboard test on 8 hours, 24 hours and 72 hours after CSF tap test were 25%, 27.9% and 39.7%. Conclusion: The positive rate of 5 meter up and go test is higher than that of 10 meter walking test, and the positive rate of 24‐hour and 72 hour comprehensive evaluation combined with walk and cognitive evaluation is higher.